An investigation of Assessing EFL Students' Sociopragmatic Competence at Diyala University - Maysaa Ridha Jawad Al Tameemi (Zanco Journal of Humanity Sciences)
The paper involves the discussion of several particular concepts related to the sociopragmatic competence of English as a Foreign Language (EFL) students of Diyala University. The quantitative research methodology was applied with the purpose of collecting data within the study and questionnaires were chosen to be the main tools for gathering data. A sample of 280 These analyses include demographic information, descriptive statistics, t-tests, and ANOVA tests in a bid to explore the sociopragmatic competence across the different genders and academic years. This research presented findings that depicted the sociopragmatic competence as moderate with significant differences regarding gender and academic progression. The female students were found to be more competent than their male counterparts, and the increase in sociopragmatic skills was progressive as the students passed from one year to another in the academically preparing years. This means that cultural sensitivity should form part and parcel of language education, and that the sociopragmatic competence has an impact on the acquisition of language. The findings of this study will contribute to the body of knowledge concerning EFL education with a focus on directed pedagogy for sociopragmatic competence.